TATA KELOLA PEMERINTAHAN DESA BINA BARU BERBASIS E-GOVERNMENT DALAM MENINGKATKAN PELAYANAN PUBLIK DI ERA INDUSTRI 4.0 - Sartika Amiruddin; Herman Dema; Haeruddin Syarifuddin (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
This study aims to determine the governance of Bina Baru Village, Kulo District, based on E-Government in improving public services in the Industrial Era 4.0 and to find out the inhibiting factors for E-Government-based public services in the Industrial Era 4.0 in Bina Baru Village, Kulo District, Sidenreng Rappang Regency. . The research population was 329 people/person and the sample was 49 people/person. The sampling technique used is purposive sampling. This type of research is descriptive quantitative. The data collection techniques used are observation, library research, questionnaires or questionnaires and documentation. The data analysis technique is in the form of descriptive statistics. The results showed that 66% of E-Government-based governance was "good", in terms of developing a reliable service system 69% good, managing government work processes 70% good, utilizing information technology optimally 62% good, developing human resource capacity 64% good. Public service 67% "good", in terms of the availability of good infrastructure 71% good, responsible to every consumer from beginning to end 66% good, able to serve quickly 58% not good, able to serve properly 66% good, able communicates 76% well. Factors that hinder public services are awareness 64% influential, 65% influential rules, 60% less influential organization, income 63% influential, 62% influential officer skills, 86% very influential facility factor.